2021
DOI: 10.3390/biom11050743
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Response of Human Breast Cancer Cells to Polyamine Modulation

Abstract: Breast cancer is a complex heterogeneous disease with multiple underlying causes. The polyamines putrescine, spermidine, and spermine are polycationic molecules essential for cell proliferation. Their biosynthesis is upregulated in breast cancer and they contribute to disease progression. While elevated polyamines are linked to breast cancer cell proliferation, there is little evidence to suggest breast cancer cells of different hormone receptor status are equally dependent on polyamines. In this study, we cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This correlates with the immune suppression we see in our studies as well as the characterization of GBM as a "cold tumor" 38 . While our studies focused on GBM, polyamines have been reported to have a protumorigenic role in established tumors in other cancerssuch as prostate and colorectaland a tumor suppressive role at the initial stages in other tumorsnamely melanoma and some types of breast cancer [39][40][41][42][43] . Therefore, our findings may be of interest to other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the immune suppression we see in our studies as well as the characterization of GBM as a "cold tumor" 38 . While our studies focused on GBM, polyamines have been reported to have a protumorigenic role in established tumors in other cancerssuch as prostate and colorectaland a tumor suppressive role at the initial stages in other tumorsnamely melanoma and some types of breast cancer [39][40][41][42][43] . Therefore, our findings may be of interest to other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated their involvement in the occurrence and development of colorectal inflammation and tumors (24)(25)(26)(27)(28)(29)(30). Additionally, the role of SCFAs in lung cancer (31), PAs in brain tumors and neuroblastoma (32, 33), SCFAs, MTCs and secondary bile acids in digestive system tumors (21,(34)(35)(36), and SCFAs, MTCs and PAs in gynecological tumors and melanoma (31,34,(37)(38)(39)(40)(41)(42) have also been confirmed. Therefore, this review focuses on the above five intestinal microbial metabolites.…”
Section: Intestinal Microbial Metabolites and Tumormentioning
confidence: 95%
“…Different effects may apply to cancer patients than to healthy individuals, especially during chemotherapy, but more research is needed [5][32]. Attempts to slow down tumor growth by inhibiting spermidine production have had little success and they have so far been limited to a few types of tumors, such as subtypes of breast cancer [33].…”
Section: Functional Foods In Health Andmentioning
confidence: 99%